Dominasi Rosatom Rusia Dalam Pasar Energi Nuklir Global - Ahmad Saifuddin Bukhari (Sospol : Jurnal Sosial Politik, 2021)
In recent years, Rosatom has dominated the world nuclear energy market. This Russian state-owned company has around 36 portfolios of new nuclear power plants (NPP) in various countries. In addition, Rosatom also controls about 17% of the nuclear fuel market. This research aims to find out how Rosatom can dominate the global nuclear energy market. To answer that, this study used a qualitative descriptive research method with the neomerkantilism concept approach. The data collection technique is done by means of literature study or literature study. The results of this study indicate that Rosatom can dominate the global nuclear energy market due to the influence and support of the Russian state. Russia made Rosatom a state-owned company aimed at pursuing maximum revenue through exports of nuclear energy for the sake of increasing the national economy as well as its global political influence.